2021
DOI: 10.1177/10567895211036491
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic, rate-dependent ductile fracture of Ti-6Al-4V alloy

Abstract: An extensive experimental campaign was run to investigate the influence of the loading direction, stress state (triaxiality ratio ranging from −0.5 to 1), and strain rate (from 10−3 to 1.5x103s−1) on the ductile fracture of Ti-6Al-4V titanium alloy. Microscopic and macroscopic observations provided some insight into the shear-driven or micro-voiding-controlled damage mechanisms prevailing at low and high triaxiality ratios, respectively. Numerical simulations were run to determine the local loading paths to fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
(85 reference statements)
1
0
0
Order By: Relevance
“…These differences must be taken into account when predicting the dynamic fracture of critical titanium structures. This conclusion is consistent with the results of SEM studies of the fracture surface of Ti-6Al-4V presented in [31]. It was shown that damage, in the form of micro-cavities, nucleated mostly at α/β interfaces.…”
Section: Discussionsupporting
confidence: 92%
“…These differences must be taken into account when predicting the dynamic fracture of critical titanium structures. This conclusion is consistent with the results of SEM studies of the fracture surface of Ti-6Al-4V presented in [31]. It was shown that damage, in the form of micro-cavities, nucleated mostly at α/β interfaces.…”
Section: Discussionsupporting
confidence: 92%